Adolescent Sexual Risk-Taking in the Informal Settlements of Nairobi, Kenya: Understanding the Contributions of Religion - Obeng Gyimah, Stephen (Journal of religion and health, 2014)
Young people in sub-Saharan Africa are at the centre of the global HIV epidemic as they account for a disproportionate share of new infections. Their vulnerability to HIV has been attributed to a myriad of factors, in particular, risky sexual behaviours. While economic factors are important, increasing attention has been devoted to religion on the discourse on sexual decision-making because religious values provide a perspective on life that often conflicts with risky sexual behaviours. Given the centrality of religion in the African social fabric, this study assesses the relationship between adolescent religiousness and involvement in risky sexual behaviours using data from the informal settlements of Nairobi. Guided by social control theory, the paper explores if and how religion and religiosity affect sexual risk-taking among adolescents.